The Ebola Virus VP30-NP Interaction Is a Regulator of Viral RNA Synthesis - Kirchdoerfer, Robert N.; Moyer, Crystal L.; Abelson, Dafna M.; Saphire, Erica Ollmann (PLoS pathogens, 2016)
Filoviruses are capable of causing deadly hemorrhagic fevers. All nonsegmented negative-sense RNA-virus nucleocapsids are composed of a nucleoprotein (NP), a phosphoprotein (VP35) and a polymerase (L). However, the VP30 RNA-synthesis co-factor is unique to the filoviruses. The assembly, structure, and function of the filovirus RNA replication complex remain unclear. Here, we have characterized the interactions of Ebola, Sudan and Marburg virus VP30 with NP using in vitro biochemistry, structural biology and cell-based mini-replicon assays. We have found that the VP30 C-terminal domain interacts with a short peptide in the C-terminal region of NP. Further, we have solved crystal structures of the VP30-NP complex for both Ebola and Marburg viruses. These structures reveal that a conserved, proline-rich NP peptide binds a shallow hydrophobic cleft on the VP30 C-terminal domain. Structure-guided Ebola virus VP30 mutants have altered affinities for the NP peptide. Correlation of these VP30-NP affinities with the activity for each of these mutants in a cell-based mini-replicon assay suggests that the VP30-NP interaction plays both essential and inhibitory roles in Ebola virus RNA synthesis.